Land Conversion for Tourism Development under Vietnam’s Ambiguous Property Rights over Land - Mai T.T. Duong; D. Ary A. Samsura; Erwin van der Krabben (Land, 2020)
The paper aims to explore the process of land conversion for tourism development in Vietnam, under the present ambiguous and insecure property rights system. Four case studies in different geographical areas were selected to analyse land conversion and land compensation for tourism projects before and after the implementation of the new land law in 2013. The findings of this study show that, in the present legal system of land and property rights, the rights of local people are not sufficiently guaranteed due to the decisive role of the State not only in defining compensation prices for land in the case of compulsory land acquisition but also in determining whether tourism projects are in the public’s interest or not (thus deciding the appropriate land conversion approach as well as affecting price negotiations). The research also found that, although a voluntary land conversion approach (when the project is not in the public’s interest), based on the 2013 Land Law, offers land users a better negotiation position and a higher compensation payment, possibly reducing land-related conflicts between the State and land users, ambiguity over property rights in fact increased due to the government’s substantial discretion to choose between ‘public purpose’ and ‘economic purpose.’ The paper concludes with questioning whether the present legal basis for compulsory land acquisition is future proof since urbanisation pressure is likely to increase, which may lead to even more land conflicts in the near future.